The Effect of Representative Account Functions and Taxpayer Trust on Tax Obligation - E. Efrianto; Bella Widyawati (Manunggal Halim Jaya, 2022)
This research was conducted with the aim of: (1) To analyze the effect of service and consulting functions on tax obligations at KPP Pratama Bangka Belitung (2) To analyze the effect of the oversight function on tax obligations at the Pratama Bangka Belitung; (3). To analyze the effect of taxpayer trust on tax obligations at the Pratama Bangka Belitung. The research method used in this study is descriptive analysis and multiple linear regression analysis, with a total sample of 88 respondents. Based on the results of multiple linear regression analysis, the results show that (1). The service and consulting functions have a positive and significant effect on tax obligations at the Tax Service Office. This can be seen from the partial test where the t count is 6,690 > t-estimated = 1,663 (2). The supervisory function has a positive and significant effect on tax obligations at the Pratama Bangka Belitung Tax Service Office with a t-calculated of 4,720 > t-estimated = 1,663 (3). Compulsory trust has a positive and significant effect on tax obligations at the Pratama Bangka Belitung Tax Service Office with a t-calculated value of t-calculated = 2,163 > t-estimated = 1,663. Simultaneously the independent variables have a significant effect on tax obligations which is indicated by the calculated f-value of 52,600 > F-table = 3.11.